Determinants of Career Development on Employee Performance - Maludin Panjaitan; Sudung Simatupang; Marto Silalahi; Julyanthry; Markus Doddy Simanjuntak (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Career development contributes significantly to organizational success by driving improved employee performance. Thus, this study aims to examine the impact of career development on employee performance. This study used a quantitative approach, involving 32 employees from the transmission and distribution engineering department. Data were collected through questionnaires. To evaluate the relationship between career development and employee performance, simple linear regression and partial hypothesis testing (t-test) were conducted using SPSS software. The research findings revealed that the instruments for career development and employee performance met the standards of validity and reliability. The regression analysis showed a positive coefficient, indicating that an increase in career development directly improves employee performance. Further partial hypothesis testing confirmed a statistically significant positive effect of career development on performance. Consequently, organizations should prioritize career development initiatives, supported by dedicated leadership and well-structured policies. By encouraging employee growth and well-being, companies can cultivate a motivated workforce, leading to a more productive and satisfying workplace.